Effects of Vouchers:Another Look at the Florida Data - Haggai Kupermintz (Arizona State University, 2001)
This report re-analyzes test score data from Florida public schools. In response to a recent report from the Manhattan Institute, it offers a different perspective and an alternative explanation for the pattern of test score improvements among low scoring schools in Florida.